The Impact of Covid 19 on the Greek Media - Papathanassopoulos, Stylianos; Antoniades, Euripides (My University, 2024)
It is widely recognized that Greece effectively managed the COVID 19 pandemic crisis through the early implementation of stringent measures and the imposition of lockdowns, similar to strategies adopted by other nations. Another noteworthy achievement was the rapid adaptation of the Greek populace to digital services. However, the situation differs in the realm of media, particularly in the context of traditional or "legacy" media. These media outlets, emerging from a decade long financial crisis marked by significant declines in advertising revenues, confronted the adverse repercussions of the COVID 19 pandemic. While there was an increase in media consumption during this period, advertising revenue experienced a substantial decline. What remains unaltered, though, is the persistent "traditional dirigist role of the Greek state" in shaping the media landscape. Adversarial media or media supporting the “Opposition” political parties as well the major Opposition accused the government of discrimination regarding the allocation of the COVID 19 public communication campaign The pandemic has reaffirmed the inclination of the Greek media to endorse an interventionist state model, even in the digital age. Much of Greece's distinctive characteristics are attributed to the prominent role the state has assumed in promoting the country's economic development. This paper aims to highlight the side effects of the COVID 19 crisis in the Greek media sector. It will also attempt to show that regardless of the changes caused due to the financial crisis and the fact that media outlets changed hands, the interplay between the Greek media and the political system still plays a pivotal role.
Keywords: Advertising; Covid; Dirigist state; Financial crisis; Legacy media; Media consumption; State aid